Density‐ and species‐dependent errors in single‐pass timed electrofishing assessment of riverine salmonids. Issue 1 (18th January 2017) - Honkanen, Hannele M.; Dodd, Jennifer A.; Fordyce, Jessica R.; Boylan, Patrick; Adams, Colin E.
Abstract: Electrofishing techniques are widely used for the estimation of the size of stream‐dwelling fish populations for both fishery management and scientific study. In contrast to multiple pass, population depletion methods, single‐pass catch‐per‐unit‐effort (CPUE) methods are less time‐consuming and labour‐intensive. A possible issue with the commonly used fixed total time CPUE protocol is that it does not differentiate between the time spent actively fishing and the time incurred while not actively fishing (e.g. removing fish from nets and navigating the site). This issue is likely related to fish density. This study compared two methods of CPUE electrofishing and tested the hypothesis that time spent handling fish and navigating a site can be a source of error in the commonly used fixed total time electrofishing method. Seventy‐one sites were sampled across three subcatchments in the Foyle catchment in Northern Ireland. We found a difference in the catch per unit time between the two methods and that this difference increased with fish density. The fixed‐time CPUE method also failed to detect a species presence in low‐density sites.